Implementing fuzzy control for a DC-DC boost converter using FPGA - Radhika, V.; Srinivasan, Karuppannan; Kiruba, R. (International Journal of Applied Power Engineering (IJAPE), 2025)
This research explores the use of field programmable gate arrays (FPGA) to mitigate static voltage errors and reduce voltage spikes in DC-DC boost converters. Given the dynamic nature of the load impedance in these converters, FPGA is well-suited for designing systems with adaptive behavior. The study implements a fuzzy control algorithm on FPGA in a simulation environment with a small sampling period. The parallel processing capability of FPGA enables the simultaneous execution of fuzzy control algorithms, enhancing the system's responsiveness to rapid changes in load conditions. This approach minimizes voltage overshoot and effectively suppresses voltage spikes. By leveraging FPGA’s high-speed parallelism and flexibility, the research demonstrates significant improvements in the dynamic performance of the DC-DC boost converter. The results highlight FPGA’s potential as a robust platform for controlling power electronic systems, ensuring improved stability and efficiency under varying load conditions.